HIV co‐infection is associated with increased transmission risk in patients with chronic hepatitis C virus. Issue 11 (4th July 2019) - Ragonnet‐Cronin, Manon; Hostager, Reilly; Hedskog, Charlotte; Osinusi, Ana; Svarovskaia, Eugenia; Wertheim, Joel O.
Abstract: Molecular epidemiological analysis of viral pathogens can identify factors associated with increased transmission risk. We investigated the frequency of genetic clustering in a large data set of NS34A, NS5A, and NS5B viral sequences from patients with chronic hepatitis C virus (HCV). Within a subset of patients with longitudinal samples, Receiver Operator Characteristic (ROC) analysis was applied which identified a threshold of 0.02 substitutions/site as most appropriate for clustering. From the 7457 patients with chronic HCV infection included in this analysis, we inferred 256 clusters comprising 541 patients (7.3%). We found that HCV/HIV co‐infection, young age, and high HCV viral load were all associated with increased clustering frequency, an indicator of increased transmission risk. In light of previous work on HCV/HIV co‐infection in acute HCV cohorts, our results suggest that patients with HCV/HIV co‐infection may disproportionately be the source of new HCV infections and treatment efforts should be geared towards viral elimination in this vulnerable population.